Bachelard et la psychanalyse de la “matière noire” (Altre Modernità, 2012)
On several occasions, Gaston Bachelard has suggested that his poetic of elements could be extended beyond the four chemical elements, notably by increasing the specificity of the material imagination related to darkness, to the nocturne element, to the material called “la ténèbre” (the darkness). According to this thinking, we propose a dual examination of some physical concepts which include the adjective "black(/dark)": the black bodies, the black holes, and the dark matters. To understand the nature of these dark thoughts, it is necessary to explain the process by which the physical transforms the meaning of the adjective, but also five free rein to a poetic digression that reveals how the dark "colours" concepts by associating them with other images. The riddle of the black body radiation is no longer simply the opportunity to explore the quantum but also the pattern of a self-awareness rêverie; the black hole is not only a singularity of the theory of general relativity but also a symbol of great depression; the dark matter is no longer just an astrophysics hypothesis but also the object of a fantasized alchemical research. Combining psychoanalysis and epistemology of knowledge about the physical "black" we hope to show how the duality of Bachelard’s philosophy responds to the provocations of material to think and dream.